Remittances and the Brain Drain Revisited: The microdata show that more educated migrants remit more - Albert Bollard; David McKenzie; Melanie Morten; Hillel Rapoport (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
Two of the most salient trends surrounding the issue of migration and development over the last two decades are the large rise in remittances, and an increased flow of skilled migration. However, recent literature based on cross-country regressions has claimed that more educated migrants remit less, leading to concerns that further increases in skilled migration will hamper remittance growth. We revisit the relationship between education and remitting behavior using microdata from surveys of immigrants in eleven major destination countries. The data show a mixed pattern between education and the likelihood of remitting, and a strong positive relationship between education and the amount remitted conditional on remitting. Combining these intensive and extensive margins gives an overall positive effect of education on the amount remitted. The microdata then allow investigation as to why the more educated remit more. We find the higher income earned by migrants, rather than characteristics of their family situations explains much of the higher remittances.
Keywords: O15; F22; J61; 330; Remittances; Migration; Brain Drain; Education